An experimental approach to assess Corbicula fluminea (Müller, 1774) resistance to osmotic stress in estuarine habitats. (5th July 2016) - Ferreira-Rodríguez, Noé; Pardo, Isabel
Abstract: Corbicula fluminea arrived in the Miño Estuary in 1989 and, from there, colonized more than 150 km upstream. Our aim was to test the capacity of C. fluminea to cope with osmotic stress conditions previously to invade new freshwater habitats through estuaries. Based on previously collected information, the experiment aims to study the response of the species to marine osmotic stress, evaluated by survival and behaviour. Experiments determined the resistance by the species to various levels of osmotic stress, and recovery time after exposure to high salinity levels, representative of the temporal and spatial salinity variation existing in the estuary. Under osmotic stress the semi-maximum response was reached after 19 days exposure. The species tolerance range, measured by individual maintained activity, was at salinity ∼20 when exposed to winter temperatures, while when animals were exposed to summer ones its tolerance was reduced to salinity lower than 15. C. fluminea show a large physiological flexibility to cope with salinity variations in estuaries. In summer, the temperature increases the metabolic rate thus making the species more vulnerable to osmotic stress exposure. These findings are relevant to preventing new invasions through ship ballast waters ensuring complete mortality if individuals are retained for >26 days. Graphical abstract: